Analysis of pedagogical approach features in physical education of pre-school aged children - Bogdanovskiy, Igor (ScienceRise: Pedagogical Education, 2016)
We know that pre-school is one of the most critical periods of human life in formation of physical health, providing its improvement, strengthening and preserving in future, so the problem of formation of pedagogical approach to physical education of children of pre-school age at classes is seen to be actual. It is shown that in a definite pre-school necessary conditions were implemented and classes with sport games were carried out taking into consideration children state of health and their preferences. It is proved that during the year children’s physical health indicators were significantly optimized –increased were the levels of physical development and percentage of harmoniously developed children, the number of children with stress adaptation mechanisms decreased, also levels of physical fitness increased and number of absenteeism due to illness reduced. It was established that professional training of future teachers-coaches in kindergartens should be based on the principles of the theory and methodology of physical education and sports and the initial state of health of pre-school aged children In whole the results occured demonstrate the effectiveness of pedagogical approach to raising interest to physical activities and improving indicators of health level and can be recommended while training pre-school children.